Consideraciones jurídico/políticas sobre la transformación agraria - Ungo, Guillermo Manuel (ECA: Estudios Centroamericanos, 1976)
No hay resúmenes disponibles.ECA Estudios Centroamericanos, Vol. 31, No. 335-336, 1976: 451-462.